Global trends of gamification in enhancing students’ social skills in physical education (2015–2025) - Rusdiyanto, Rajip Mustafillah; Kurniawan, Ari Wibowo (Physical Education and Sports: Studies and Research, 2025)
Background: The development of digital technology has triggered a more interactive learning transformation through gamification, namely using game elements to increase students' motivation, engagement, and social skills, such as cooperation, communication, empathy, and problem solving. Objectives: This study aims to analyze global research trends on gamification in enhancing students' social skills, particularly in physical education, through a bibliometric analysis from 2015 to 2025. Methods: This study employed a bibliometric design. Data were retrived from the Scopus database on April 22, 2025, using specific keywords: (gamification OR gamified learning OR game-base-based learning) AND ("physical education" OR "PE class" OR "sport education") AND (social skills" OR "social competence" OR "social interaction") AND (elementary school" OR "primary school" OR "midle school" OR "junior high school" OR "high school" OR "secondary school" From an initial 120 documents, 47 met the inclusion criteria. VOSViewer was used to analyze keyword co-occurrence, visualize trends, and identify thematic clusters by completely counting on all keywords with at least two documents per author. Results: 47 relevant articles were identified, with publication peaking in 2020. Keyword analysis revealed five main thematic clusters: gamification in education, digital game-based learning, collaborative learning, emerging technologies, and motivation. The most frequent keywords were game-based learning (n=12), gamification (n=9), and students (n=8). The University of Patras emerged as the most productive institution, while the leading journal was the International Journal of Learning, Teaching and Educational Research. Conclusions: Although research on gamification has grown significantly, its application in physical education remains underexplored. This study reveals a gap in leveraging gamification to develop students' social skills in physical education. Future research should focus on integrating gamification in this context while considering sociocultural and technological factors to ensure inclusive and effective implementation.